Study of Electronic, Thermodynamic and Vibrational Properties of SnO2 Nanoparticles with Different Stoichiometries and Effect of Nonhydrostatic Pressure - Caravaca, Maria de Los Angeles Dominga (2018)
High pressure behavior of SnO2 nanoparticles of 3nm is studied up to 19 GPa using ab initio method. First, elecgtronic strcuture equilibrium configuration, elastic and vibrational properties are performed on nanoparticles with different stoichiometries and at normal external pressure. The results are used to evaluate the contribution of the stoichiometry on the surface energy and on the relative stability for different operation condition of temperatura and oxygen partial pressure. Secondly, in order to get microscopic description of the shell size and nature of the disorder found with Raman Spectrocsopy (RS) in NP of 2.8 nm under high pressure, we introduce in the calculation external non hydrostatic pressure as applied in the RS experiment. The change in the structural properties is analyzed. We calculated for the first time the vibrational density of state of the nanoparticle for different stoiciometries and compared with the Raman spectrum obtained for the same size. The purpose is to know if it is possible to determine the probable stoiciometry of the nanoparticles studied experimentally. In addition, the frequencies of vibration of a free nanoparticle in one spheroidal mode are calculated in the frozen phonon approach.